Teacher's role and challenges in pandemic times through a virtual learning environment (classroom) (2021)
The investigation was carried out with a qualitative approach and under the case study method, which aimed to know the changes that have occurred in the role of teachers, as well as the main challenges that, in times of pandemic, it brings to them the use of VLE (Virtual Learning Environments) in the development of their work. The results of this work show that the challenges that teachers have faced when implementing remote education, have to do mainly with the evaluation processes, the affective relationships that involve students and teachers, and the adoption of new teaching methodologies. Key words: Remote education, pandemic, COVID-19, Critical Digital Literacy, Virtual Learning Environments, teacher’s role, teaching challenges.